2003
DOI: 10.1136/jnnp.74.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Limb length and dementia in an older Korean population

Abstract: Objectives: There has been little research into risk factors for dementia outside Western settings, in particular the importance of early life nutrition as estimated by adult body size. This study investigated the associations of arm and leg length with cognitive impairment and dementia in a community sample of older Korean people. Methods: 746 community residents aged 65 or over were clinically assessed for dementia and cognitive impairment. The following were also measured: arm length (demispan), leg length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
81
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 40 publications
(19 reference statements)
11
81
2
Order By: Relevance
“…The structural equation analysis also demonstrated that height had a positive association with central nervous system function. Similar relationship has been previously described in older adults, in cross-sectional as well as prospective studies, particularly with respect to cognitive function [1,22]. Interestingly, we could not find an evidence of the positive relationship between Inflammatory Markers and Central Nervous System function.…”
Section: Discussionsupporting
confidence: 85%
“…The structural equation analysis also demonstrated that height had a positive association with central nervous system function. Similar relationship has been previously described in older adults, in cross-sectional as well as prospective studies, particularly with respect to cognitive function [1,22]. Interestingly, we could not find an evidence of the positive relationship between Inflammatory Markers and Central Nervous System function.…”
Section: Discussionsupporting
confidence: 85%
“…We found that a longer reproductive period was associated with a significantly better cognitive function (MMSE), in agreement with the majority of previous studies [10][11][12]. Other studies [20][21][22] also reported the similar effect of reproductive period on the risk of dementia and AD, but not all studies [13,23,24]. Our finding supported the protective effect of estrogen exposure on cognitive impairment.…”
Section: Discussionsupporting
confidence: 82%
“…An association between older motherhood and better cognitive functioning in later life was also reported in a study of Chinese older women (Heys et al, 2011). However, a Korean study found no association between age at first birth and dementia (Kim et al, 2003). Conclusions from these investigations are thus inconsistent probably reflecting the range of study populations and designs used, the fact that several were based on clinical or otherwise nonpopulation representative samples, included only women and had limited control for relevant socioeconomic and psychosocial factors.…”
Section: Previous Researchmentioning
confidence: 68%
“…However, other studies have found no or different associations. These include studies of representative samples of French (Ryan, Carrière, Scali, Ritchie, & Ancelin, 2009) and Australian (Low, Anstey, Jorm, Rodgers, & Christensen, 2005) women and small or clinically based samples of women in Southern California (Smith et al, 1999), Canada (Hesson, 2012), and Korea (Kim, Stewart, Shin, & Yoon, 2003). In a Swedish study of older female twins, high parity was associated with cognitive impairment in a case-control analysis but not in a comparison of discordant twin pairs (Rasgon et al, 2005).…”
Section: Previous Researchmentioning
confidence: 99%